The Breeding System of Kacangma and the Effect of Drying Processes on the Leaf’s Flavonoids Content - Saban, Flora Eliza (Universiti Malaysia Sarawak (UNIMAS), 2015)
Leonurus sibiricus is an annual herb that belongs to the family Lamiaceae. In Malaysia, there are two species found, namely Leonurus sibiricus L. (pink-flowered variety) and Leonurus japonicus Houtt (white-floured variety). Both of these species are easy to distinguish by colour, however, both of them do not differ much based on their vegetative characteristics and also their phytochemical content. Pollen happens to be an important vector of gene flow in plants. In the current study, it showed that the pollen viability might affect greatly due to the concentrations of culture media (agar) used and the duration of incubation. Both of these conditions exhibited negative correlation with the viability tests done on L. sibiricus. In the phytochemical analysis, the current study showed that the flavonoids compounds in L. sibiricus were growth stage dependent, hence the medicinal values may differ based on their growth stages. In addition, the current study also showed the effects of different drying methods on the L. sibiricus leaves. Sun-dried leaves exhibited more compound contents and antioxidant capacity compared to air-dried leaves, whereas the exposure of oven-drying on the L. sibiricus leaves have caused antioxidant loss due to the heat instability compounds.